2014
DOI: 10.1186/1746-6148-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of Clostridium difficile isolated from European Barn Swallows (Hirundo rustica) during migration

Abstract: BackgroundClostridium difficile is an important bacterial pathogen of humans and a variety of animal species. Birds, especially migratory passerine species, can play a role in the spread of many pathogens, including Clostridium difficile. Barn Swallows (Hirundo rustica) nest in close proximity to human habitats and their biology is closely associated with cattle farming. Therefore, we hypothesized that Barn Swallows can be the reservoir of Clostridium difficile.ResultsBarn Swallows (n = 175) were captured on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
11
2
Order By: Relevance
“…These results were in line with those from a previous study that found C. difficile in faeces from wild birds (house sparrows) trapped in or close to pig farms (Burt et al 2012). Interestingly, other bird species have also found positive for ribotypes which are commonly found in farm animals and humans (Bandelj et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results were in line with those from a previous study that found C. difficile in faeces from wild birds (house sparrows) trapped in or close to pig farms (Burt et al 2012). Interestingly, other bird species have also found positive for ribotypes which are commonly found in farm animals and humans (Bandelj et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…As observed in other infections such as salmonellosis (Andr es et al 2013), wild birds in close contact with pig farms may be at higher risk of harbouring the pathogens present in the farm, especially if the farm environment appears to be highly contaminated. These results differed from those from other European countries, including Spain, in which C. difficile was not found in wild birds or was isolated from only a few samples (Alderete 2011;Bandelj et al 2011Bandelj et al , 2014. However, in these studies, most of the sampled birds were not related to pig farming.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, different studies have investigated the presence of the bacterium in wild animals, including wild passerine birds (Bandelj et al 2011) and barn swallows (Bandelj et al 2014); zoo animals (chimpanzees, dwarf goats, Iberian ibexes and plains zebras) (Á lvarez-Pérez et al 2014); sea otters (Miller et al 2010); free-living South America coatis (Silva et al 2014); small and medium-size wild mammals (raccoons, shrews, deer and house mice, rats, voles, opossum and groundhogs) (Jardine et al 2013); black and Norway rats (Firth et al 2014;Himsworth et al 2014); feral pigs (Thakur et al 2011) and Iberian free-range pigs (Á lvarez-Pérez et al 2013).…”
mentioning
confidence: 99%